2019
DOI: 10.1021/acs.iecr.8b04849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging Treatment on the Hydrotreating Performance of the Unsupported Catalyst

Abstract: An unsupported Ni−Mo−W catalyst was synthesized by the hydrothermal method and treated by an aging treatment to improve its specific surface area and pore size. The effect of different aging conditions was studied by BET, XRD, SEM, and HRTEM techniques. The catalytic activity of the unsupported catalyst was evaluated with a simulated diesel feed. BET results showed that the catalyst specific surface area and pore volume increased significantly after aging treatment, and the hydrotreating results revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The sulfidation reagent is difficult to enter the inner of the unsupported catalysts due to its lower pore distribution, and only the active components distributed on the outer surface are sulfided, which greatly reduces the utilization rate of the active component and causes great waste. To increase the specific surface area and pore distribution of the unsupported hydrogenation catalysts, a pore-expanding agent, such as methylcellulose, was added before forming by Yin et al [17], which produces more pore structures for the unsupported hydrogenation catalysts after calcination. In addition, hydrothermal aging was also used to treat the unsupported catalyst precursors to improve the dispersion of the active components [17], and the results showed that the specific surface area, pore volume, and average pore diameter of the unsupported catalysts were obviously improved after aging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sulfidation reagent is difficult to enter the inner of the unsupported catalysts due to its lower pore distribution, and only the active components distributed on the outer surface are sulfided, which greatly reduces the utilization rate of the active component and causes great waste. To increase the specific surface area and pore distribution of the unsupported hydrogenation catalysts, a pore-expanding agent, such as methylcellulose, was added before forming by Yin et al [17], which produces more pore structures for the unsupported hydrogenation catalysts after calcination. In addition, hydrothermal aging was also used to treat the unsupported catalyst precursors to improve the dispersion of the active components [17], and the results showed that the specific surface area, pore volume, and average pore diameter of the unsupported catalysts were obviously improved after aging.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the specific surface area and pore distribution of the unsupported hydrogenation catalysts, a pore-expanding agent, such as methylcellulose, was added before forming by Yin et al [17], which produces more pore structures for the unsupported hydrogenation catalysts after calcination. In addition, hydrothermal aging was also used to treat the unsupported catalyst precursors to improve the dispersion of the active components [17], and the results showed that the specific surface area, pore volume, and average pore diameter of the unsupported catalysts were obviously improved after aging. At the same time, the hydrotreating activity was greatly improved.…”
Section: Introductionmentioning
confidence: 99%